2000
DOI: 10.1002/(sici)1096-9071(200004)60:4<446::aid-jmv13>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

A neutralizing recombinant human antibody Fab fragment against Puumala hantavirus

Abstract: A combinatorial human antibody Fab pComb3H library, generated from splenic lymphocytes of a Puumala hantavirus (PUUV) immune individual, was selected against PUUV using the phage display technique. Panning was carried out with antigens immobilized by MAbs directed to the two PUUV envelope glycoproteins G1 and G2. Thirteen Fabs, with reactivity directed to PUUV and specifically the G2 protein, as assessed by immunofluorescence and ELISA respectively, were isolated in crude preparations. By a focus reduction neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…In subsequent studies with the same Mabs, sequence analysis of the genomes of Mab escape mutants revealed that noncontiguous amino acids form neutralizing epitopes (i.e., conformational epitopes) on the envelope proteins [Wang et al, 1993;Kikuchi et al, 1998]. Conformational, neutralizing epitopes were also identified on PUUV using phage display to express random peptides and by reacting the expression products with two G2-specific Mabs to PUUV [Salonen et al, 1998, Heiskanen et al, 1999, Nicacio et al, 2000. Thus, evidence to date suggests that neutralizing epitopes of the G1 and G2 proteins of HFRS-causing hantaviruses are frequently conformational.…”
Section: Introductionmentioning
confidence: 99%
“…In subsequent studies with the same Mabs, sequence analysis of the genomes of Mab escape mutants revealed that noncontiguous amino acids form neutralizing epitopes (i.e., conformational epitopes) on the envelope proteins [Wang et al, 1993;Kikuchi et al, 1998]. Conformational, neutralizing epitopes were also identified on PUUV using phage display to express random peptides and by reacting the expression products with two G2-specific Mabs to PUUV [Salonen et al, 1998, Heiskanen et al, 1999, Nicacio et al, 2000. Thus, evidence to date suggests that neutralizing epitopes of the G1 and G2 proteins of HFRS-causing hantaviruses are frequently conformational.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies measure antibody efficacy through the focus reduction neutralization test (FRNT) and hemagglutination inhibition (HI) test at the cellular level, as well as animal experiments against lethal hantavirus challenge (sucking mice or newborn rat models for HTNV or SEOV infection and hamster models for ANDV or SNV infection) (Zhang et al, 1989;Xu et al, 2002;Manigold and Vial, 2014). For old world hantaviruses, 13 crude Fab preparations directed to the PUUV Gc protein were generated from splenic lymphocytes of a PUUV-immune individual and exhibited type-specific neutralization of PUUV, with a 44-54% reduction in FRNT (de Carvalho Nicacio et al, 2000). Anti-SR-11 (SEOV) rat serum applied 4 h before or 72 h after the challenge could protect against lethal SR-11 (SEOV) infection in newborn rats, and cross-protection effects were also found against KI-262 (SEOV) and 76-118 (HTNV) (Zhang et al, 1989).…”
Section: Blocking Viral Entrymentioning
confidence: 99%
“…In proliferation examination, T lymphocytes that are immunized with heterogenic r Ns were successfully recollected by PUUV rN in vitro, similarly animals T lymphocytes were immunized with homologous proteins. Subunit vaccines hold advantages like safety, easy production, and absence of interference between components of the multivalent formulation [8,50,51].…”
Section: Sub-unit Vaccinesmentioning
confidence: 99%